ANALISIS PEMAHAMAN KONSEP SISWA PADA MATERI FLUIDA STATIS MENGGUNAKAN RANKING TASK EXERCISE - Wardaningsih, Retno Suko; Supriyatman, Supriyatman (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to describe students' conceptual understanding of static fluids using the Ranking Task Exercise. This research was conducted at SMA Negeri 1 Rio Pakava in class XI IPA 3 consisting of 24 students. This research was a qualitative research. Data were based on existing facts, so that in this study a qualitative descriptive approach was used. The data collection instruments used were essay tests and interviews. Respondents were selected based on the ability level of students which were divided into high, medium and low categories. Based on the results of the study, it shows that students' understanding of the concept of static fluids using the Ranking Task Exercise was still relatively low. Students do not understand that the concept of Archimedes' law was different from the concept of hydrostatic pressure and seems to equate that Archimedes' law is also hydrostatic pressure. Students memorized Pascal's law but did not understand the concept thoroughly. In addition, the most dominant students understand the concept for hydrostatic pressure material. While most students do not understand the concepts for Pascal's law material.